Highly stable electronic properties of rippled antimonene under compressive deformation - Tian, Yujia (2022)
Antimonene has attracted much attention for its high carrier mobility and suitable band gap for electronic, optoelectronic, and even spintronic devices. To tailor its properties for such applications, strain engineering may be adopted. However, such 2D crystals may prefer to exist in the rippled form due to the instability of long-range orders, and rippling has been shown to have a contrasting, significant impact on the electronic properties of various 2D materials, which complicates the tuning process. Hence, the effects of rippling on the electronic properties of antimonene under strain are herein investigated by comparing antimonene in its rippled and flat forms. DFT calculations are performed to compute the structural and electronic parameters, where uniaxial compression of up to 7.5% is applied along the armchair and zigzag directions to study the anisotropic behavior of the material. Highly stable properties such as the work function and band gap are obtained for the rippled structures, where they are fully relaxed, regardless of the compression level, and these properties do not deviate much from those of the pristine structure under no strain. In contrast, various changes are observed in their flat counterparts. The mechanisms behind the different results are thoroughly explained by analyses of the density of states and structure geometry. The out-of-plane dipole moments of the rippled structures are also presented to give further insights into potential applications of rippled antimonene in sensors, actuators, triboelectric nanogenerators, etc. This work presents extensive data and thorough analysis on the effect of rippling on antimonene. The identification of optimal ripple amplitudes for which the electronic properties of the pristine condition can be recovered will be highly significant in guiding the rational design and architecture of antimonene-based devices.